Efektivitas Brand Ambassador, Label Halal, dan Loyalitas Merek Terhadap Kepuasan Konsumen pada Produk Natasha Skin Care di Sidoarjo Effectiveness of Brand Ambassador, Halal Labels and Brand Loyalty on Costumers Satisfaction on Natasha Skin Care Products in Sidoarjo - Hesti Vidiastutik; Misti Hariasih (ITB AAS Indonesia Surakarta, 2023)
The purpose of this study aims to determine the effect of brand ambassador, halal labels and brand loyalty on consumer satisfaction with Natasha Skin care product in Sidoarjo. Research using quantitative methods using descriptive research types. Sampling in this study used the Random Sampling method with a total sample of 96 respondents, This study uses data collection techniques by distributing questionnaires. The data analysis technique used in this study is multiple linier regression analysis using the SPSS Statistic 25 statistical tool. The results of this study indicate that Brand Ambassador have a significant effect on consumer satisfaction, Label halals and Brand Loyalty have a significant effect on consumer satisfaction on products Natasha Skin Care in Sidoarjo city.